Exploring the Relationships of Learners and Instructors in Online Courses - Conklin, Sheri; Oyarzun, Beth; Kim, Stella; Garrett Dikkers, Amy (Online Learning, 2024)
This quantitative study explored the relationship between student-instructor connectedness and student anxiety in online higher education courses. Research shows the value of student-instructor connectedness for student satisfaction in online learning. Utilizing the Connectedness and Anxiety items of the Student-Instructor Relationship Scale (Creasey, et al., 2009) in a large-scale cross-sectional survey with a representative sample of students at a comprehensive research university in the southeastern United States of America, we found significant relationships between the dependent variables (connectedness, anxiety, and motivation). Students with higher connectedness with instructor(s) tended to have higher motivation with lower levels of anxiety. In addition, students with higher anxiety were likely to show lower levels of motivation. Students perceived male instructors to form lower connectedness and male students and transfer students had higher levels of anxiety. Findings contribute to the field of instructor connectedness in online learning and have implications for higher education institutions and faculty considering increasing online learning offerings. We provide recommendations for building rapport and enhancing connectedness in online learning to decrease anxiety and increase student motivation.